Language Curriculum Innovation: Exploring the RPL Students’ Respond of Factors of BL Adoption in Higher Education - Budiyanti, Kurnia; Syarif, Hermawati; Zainil, Yetti (Universitas Pahlawan Tuanku Tambusai, 2023)
Blended learning (BL) is a demand for curriculum innovation. The need of BL for working students is avoidable. This research investigates the respond of the Recognition of Past Learning (RPL) program students of factor that influence students toward blended learning adoption in higher education. This research employed quantitative method with survey design. The subjects of the research were 25 of RPL students. To collect the data, the researcher used questionnaires with Likert scale. The data analysis was descriptive statistics. Results showed that 84% RPL students preferred BL setting. The students also manifested a positive respond of each factors of the blended learning adoption in their campus. Thus, positive support factors, students’ attitude, students’ perspective, and learning effectiveness regarding blended learning adoption has positive contribution to innovate curriculum development especially for RPL class.Keywords: blended learning, curriculum, innovation, respond